Prefrontal-Temporal Pathway Mediates the Cross-Modal and Cognitive Reorganization in Sensorineural Hearing Loss With or Without Tinnitus: A Multimodal MRI Study - Luan, Ying; Wang, Congxiao; Jiao, Yun; Tang, Tianyu; Zhang, Jian; Teng, Gao-Jun (Frontiers in Neuroscience, 2019)
Objective: Hearing loss, one main risk factor of tinnitus and hyperacusis, is believed to involve significant central functional abnormalities. The recruitment of the auditory cortex in non-auditory sensory and higher-order cognitive processing has been demonstrated in the hearing-deprived brain. The dorsolateral prefrontal cortex (dlPFC), which has dense anatomical connections with the auditory pathway, is known to play a crucial role in multi-sensory integration, auditory regulation, and cognitive processing. This study aimed to verify the role of the dlPFC in the cross-modal reorganization and cognitive participation of the auditory cortex in long-term sensorineural hearing loss (SNHL) by combining functional and structural measurements. Methods: 35 patients with long-term bilateral SNHL and 35 matched healthy controls underwent structural imaging, resting-state functional magnetic resonance imaging (rs-fMRI), diffusion tensor imaging (DTI), and neuropsychological assessments. Ten SNHL patients were with subjective tinnitus. Results: No differences in gray matter volume, spontaneous neural activity, or diffusion characteristics in the dlPFC were found between the SNHL and control groups. The functional connectivity (FC) between the dlPFC and the auditory cortex and visual areas, such as the cuneus, fusiform, lingual cortex, and calcarine sulcus was increased in patients with SNHL. ANOVA and post hoc tests revealed similar FC alterations in the SNHL patients with and without tinnitus when compared with the normal hearing controls, and SNHL patients with and without tinnitus showed no difference in the dlPFC FC. The FC in the auditory cortex was associated with the symbol digit modality test (SDMT) scores in the SNHL patients, which reflect attentional function, processing speed, and visual working memory. Hearing-related FC with the dlPFC was found in the lingual cortex. A tract-based spatial statistics (TBSS) analysis revealed decreased fractional anisotropy (FA) values, mainly in the temporal inferior fronto-occipital fasciculus (IFOF), which showed remarkable negative correlations with the mean hearing thresholds in SNHL. Conclusion: Higher functional coupling between the dlPFC and auditory and visual areas, accompanied by decreased FA along the IFOF connecting the frontal cortex and the occipito-temporal area, might mediate cross-modal plasticity via top-down regulation and facilitate the involvement of the auditory cortex in higher-order cognitive processing following long-term SNHL.